2015
DOI: 10.1158/1078-0432.ccr-14-0519
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Alterations in the RB Pathway Indicate Prognostic Outcomes of Early-Stage Lung Adenocarcinoma

Abstract: Purpose: To better understand the complete genomic architecture of lung adenocarcinoma.Experimental Design: We used array experiments to determine copy number variations and sequenced the complete exomes of the 247 lung adenocarcinoma tumor samples along with matched normal cells obtained from the same patients. Fully annotated clinical data were also available, providing an unprecedented opportunity to assess the impact of genomic alterations on clinical outcomes.Results: We discovered that genomic alternatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…There have been prior studies looking at the clinical correlation of RB1 in NSCLC with varying results, summarized in Table . The largest of these by Choi et al used DNA sequencing and identified RB1 mutant status to be associated with shorter disease‐free survival only in early stage adenocarcinoma . The incidence of RB1 mutation of 5.9% in their cohort is comparable to ours.…”
Section: Discussionsupporting
confidence: 76%
“…There have been prior studies looking at the clinical correlation of RB1 in NSCLC with varying results, summarized in Table . The largest of these by Choi et al used DNA sequencing and identified RB1 mutant status to be associated with shorter disease‐free survival only in early stage adenocarcinoma . The incidence of RB1 mutation of 5.9% in their cohort is comparable to ours.…”
Section: Discussionsupporting
confidence: 76%
“…TP53 was most prevalent among the somatically mutated genes detected in this IPF-LC cohort (22/35, 62.9%) irrespective of tumour subtype (P = 0.157), which is similar to the findings of prior studies conducted in the general LC population (55.5% Korean, Fisher's exact P = 0.533; 72.8% TCGA, P = 0.3) [16,17,36]. Ten somatic mutations in TP53 were located in a previously known recurrent hotspot [37], with the majority of them occurring in the p53 DNA-binding domain and the p53 tetramerization motif, except for four truncating mutations (Figure 2A).…”
Section: Significantly Mutated Genes In Ipf-lcsupporting
confidence: 87%
“…To compare gene mutation frequencies of IPF‐LC samples with those of the control group, clinical and genomic data were additionally obtained from the two previous studies conducted in Korean non‐small‐cell lung cancer (NSCLC) patients and The Cancer Genome Atlas (TCGA) Network. The number and the composition of tumour samples according to the histological subtype in the control group were determined on the basis of the proportion of each histological subtype among all of the IPF‐LC samples.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that CNV pattern in cfDNA could mirror the primary tumors of prostate and breast cancer 37 , 38 , suggesting CNV in cfDNA might act as a surrogate of primary tumor. Clinical application of cfDNA CNV has been extensively explored and most of the studies focused on the relationship between CNV of specific genes with clinicopathological features or prognosis in NSCLC 39 , 40 . Recently, Louise and colleagues examined the CNV in circulating tumor cells (CTC) from pretreatment blood samples of small cell lung cancer (SCLC) patients and reported that CNV-based classification could distinguish chemosensitive from chemorefractory cases with an accuracy of 83.3% 41 .…”
Section: Discussionmentioning
confidence: 99%